Enzymes and cytokines disease in total hip arthroplasty: promoters of immune loosening - Victorino Pacheco-Martelo; Sebastián Roldán-Vasco (Revista de la Facultad de Medicina, 2018)
Introduction: An important cause of hip prosthesis failure is loosening related to cytokine-mediated release of enzymes that produces lysis of the bone that supports the implant. Objective: This paper aims to describe the biological interaction mechanisms of the molecules that promote total hip prosthesis loosening, the most frequent problem observed during the process. Materials and methods: The authors conducted a literature search in the PubMed and Scopus databases for original articles and clinical cases with no filters by publication date. MeSH terms hip prosthesis loosening, aseptic loosening, cytokines, and hip arthroplasty failure were used. Data were extracted from 250 studies, of which 66 were representative for this review and were selected for writing purposes. Results: The most representative molecules involved in hip prosthesis loosening are described, and the interactions between them are presented. Conclusions: Enzymes and cytokines have been widely studied for four decades, although their interaction mechanisms are still misunderstood. In consequence, an interaction mechanism, which may be called “enzymes and cytokines disease” or “immune loosening”, is proposed.